RNA-seq based integrative analysis of potential crucial genes and pathways associated with patellar instability. Issue 5 (2nd May 2022) - Xu, Chenyue; Dong, Zhenyue; Ji, Gang; Yan, Lirong; Wang, Xiaomeng; Li, Kehan; Liu, Junle; Zhao, Juan; Wang, Fei
ABSTRACT: Patellar instability (PI) is a common knee injury in adolescents, but the crucial biomarkers and molecular mechanisms associated with it remain unclear. We established a PI mouse model and investigated PI-related changes in gene expression by RNA sequencing (RNA-seq). Differentially expressed gene (DEG) analysis and enrichment analysis were performed to identify crucial genes and pathways associated with PI. Subsequently, a protein-protein interaction, DEG-miRNA, DEG-transcription factors, and DEG-drug interaction networks were constructed to reveal hub genes, molecular mechanism, and potential drugs for PI. Finally, the reliability of the sequencing results was confirmed by real-time quantitative polymerase chain reaction (RT-qPCR) and immunohistochemistry. Upon comparison with the control group, 69 genes were differently expressed in PI, including 17 upregulated and 52 downregulated ones. The DEGs were significantly enriched in Janus kinase (JAK)/signal transducer and activator of transcription (STAT) signaling pathway and immune responses. The protein–protein interaction network identified ten PI-related hub genes, all of which are involved in the JAK/STAT signaling pathway or inflammation-related pathways. DEG-miRNA and DEG-transcription factor networks offered new insights for regulating DEGs post-transcriptionally. We also determined potential therapeutic drugs or molecular compounds that could restore dysregulated expression of DEGs via the DGIdb database. RT-qPCR results were consistent with the RNA-seq, confirming the reliability of the sequencing data. Immunohistochemistry results suggested that JAK1 and STAT3 expression was increased in PI. Our study explored the potential molecular mechanisms in PI, provided promising biomarkers and suggested a molecular basis for therapeutic targets for this condition. GRAPHICAL ABSTRACT: uf0001